Pemberdayaan Pemuda dalam Meningkatkan Kesejahteraan Keluarga Desa Giripurwo Kabupaten Kulon Progo - Eko Wahyunanto Prihono; Tri Siwi Nugrahani; Catur Endang Setyaningrum (Jurnal Pemberdayaan Masyarakat, 2022)
This study aims to describe the empowerment of youth organization in improving family welfare through the cultivation of cardamom plants and the use of livestock waste as organic fertilizer. This research is a quantitative descriptive study in which the researchers collect information related to the development of agricultural potential in Giripurwo Village. The research subjects were the hamlet chief, the youth organization chief, the youth organization members and the community of Bulu Hamlet, Giripurwo Village. The sampling technique was carried out by using the snowball sampling. Data collection techniques in this study used questionnaires and interview guidelines. Data analysis was carried out through quantitative descriptions and then categorized it through percentages. The results showed that the empowerment of youth organization was carried out through: 1) counseling about development had an average of 80% (good category), 2) training activities had an average of 74% (good category), 3) coaching activities had an average of 86% (very good category), and 4) role increasing had an average of 77% (good category). Overall, this empowerment program showed that 79% (good category) was appropriate. Youth organization are able to process livestock waste into organic fertilizer and develop agricultural potential through cardamom cultivation. In addition, there is a commitment from the participants to manage the knowledge and skills acquired during the activity and the implementation of these activities continuously in order to improve family welfare.